Synthesis and characyerization of polymeric nanopracticles and thin films - Khoh, Wai Hwa. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This project focuses on the synthesis and characterization of colloidal polypyrrole and starch-based microgels. The colloidal polypyrrole were synthesized through the chemical polymerization of pyrrole with FeC13.6H20 in aqueous solution of methycellulose. Colloidal polypyrrole were being characterized with respect to its particle morphology, particle sizes, stability, chemical structure and electrochemical properties. tarch-based microgels were synthesized in the water in oil emulsion using epichlorohydrin (ECH) as the cross-linker. These microgels were being characterized with respect to their morphology, particle sizes, pasting characteristic and chemical structure. Colloidal polypyrrole appeared to be globular in shape, 100-580 run in diameter and readily formed aggregations in water. Starch-based microgels were observed to be spherical in shape and of much reduced granule size than native starches. Results of FTIR and UV-VIS showed that both colloidal polypyrrole and the starch microgel samples possessed very similar physical and chemical properties but distinctively different from their original materials. The RV A results showed significant decrease in viscosity of the cross-linked starch microgels as compared to that ofthe native starches.